It Takes a Village: Holistic Emancipatory Framework for Students of Color in Study Abroad (Comparative & International Education Series, 2021)
African American and Latino students continue to remain underrepresented in American study abroad programs.  Building on emancipatory frameworks (i.e. double consciousness/multiple consciousness, critical race theory, and Sen’s capability approach), a new conceptual framework is introduced under the acronym MENSCH which involves identifying multiple consciousness, exploring identity intersections, naming power structures, investigating study abroad contexts, using the capability approach, and highlighting knowledge, skills, and abilities. The chapter then deconstructs the acronym to illustrate how MENSCH can pragmatically be adapted in support of underrepresented students (including Latino and African American students).  This model also rejects frequently utilized deficit perspectives to work holistically and systemically towards building more inclusive study abroad programs and student experiences.